Positions of the summer ice edge and autumn dates of stable ice formation in the Laptev, East-Siberian and Chukchi seas in 1981–2018 - A. G. Egorov (Лëд и снег)
The spatial and temporal variability of ice edge position at the end of the summer period, the dates of the beginning of stable ice formation in early autumn in the Russia’s Eastern Arctic seas (Laptev, East-Siberian, and Chukchi) during 1981–2018 together with climate changes in the 21st century are analyzed. The analysis of summer and autumn ice characteristics shows certain common features occurring for many years: since the beginning of the 21st century, ice conditions have significantly improved, which is due to the more Northern position of the ice border in August–September and later dates for the beginning of stable ice formation in September–October. On average for the period 2002–2018, the ice edge at the end of the period of clearance from ice shifted (as compared to 1981–2001) in a northerly direction by about 400–500 km. Observations did show that in 2003–2018, the beginning of stable ice formation in the autumn season (as compared to 1981–2002) occurred later by about three weeks. The maximum northward shift of the ice edge was first observed (since 2002) on the aquatory to the East of the New Siberian Islands, and then (since 2011) – to the West of them. The greatest anomalies of late dates (onset) of ice formation were first observed (since 2003) in the Chukchi Sea, then (since 2008) – in the Laptev Sea, and later (since 2014) – again in the Chukchi Sea. Long-term changes in the ice conditions occur according to the similar scenario: first, an anomaly of the latitudinal position of the edge or the date of the ice formation beginning was formed in the Eastern part of the studied aquatory, and then this anomaly shifted from East to West. At the same time, the anomaly diminishes in the East that makes it possible to interpret the observed natural changes as fluctuations of the «ice wave» type. Taking into account the wave features of changes in summer and autumn ice indicators, we can assume that in the 2020s we should expect a similar continuation of natural fluctuations in changes in ice conditions, which will be accompanied by a spatial shift of the ice edge in the South direction and relatively earlier dates for the beginning of ice formation.